-3x^2-2x (+-)6=0
ax^2+bx+c
a=-3
b=-2
c= either positive or negative 6 (there is no plus or minus in your question.)
What are the answer choices? It might help.
a and c i think
the blue circle is all the people who had brothers one name was in the blue circle so one person had a brother but the in between part of the too circles are who had both a brother and a sister so the is one name in the between purple so you count that one to for brother and for sisters
there were 2 people that had brother
and four people that had sisters
and one that had both
(1)Identify the surface whose equation is r = 2cosθ by converting first to rectangular coordinates...(2)Identify the surface whose equation is r = 3sinθ by converting first to rectangular coordinates...(3)Find an equation of the plane that passes through the point (6, 0, −2) and contains the line x−4/−2 = y−3/5 = z−7/4...(4)Find an equation of the plane that passes through the point (−1,2,3) and contains the line x+1/2 = y+2/3 = z-3/-1...(5)Find a) the scalar projection of a onto b b) the vector projection of a onto b given = 〈2, −1,3〉 and = 〈1,2,2〉...(6)Find a) the scalar projection of a onto b b) the vector projection of a onto b given = 〈2,1,4〉 and = 〈3,0,1〉...(7)Find symmetric equations for the line of intersection of the planes x + 2 y + 3z = 1 and x − y + z = 1...(8)Find symmetric equations for the line of intersection of the planes x + y + z = 1 and x + 2y + 2z = 1...(9)Write inequalities to describe the region consisting of all points between, but not on, the spheres of radius 3 and 5 centered at the origin....(10)Write inequalities to describe the solid upper hemisphere of the sphere of radius 2 centered at the origin....(11)Find the distance between the point (4,1, −2) and the line x = 1 +t , y = 3 2−t , z = 4 3−t...(12)Find the distance between the point (0,1,3) and the line x = 2t , y = 6 2−t , z = 3 + t...(13)Find a vector equation for the line through the point (0,14, −10) and parallel to the line x=−1+2t, y=6-3t, z=3+9t<span>...</span>
Answer:
y = -(x + 2)² + 1
Step-by-step explanation:
Parent function given in the graph is a quadratic function,
f(x) = x²
Since, graph is opening downwards transformed function of the preimage will be,
g(x) = -x²
This transformed function is shifted further by 2 units left horizontally and 1 unit upwards.
Therefore, rule for the transformation will be,
g(x) → h[(x + 2), (y + 1)]
By this rule transformed function will be,
h(x) = -(x + 2)²+ 1
Equation of the curve will be,
y = -(x + 2)² + 1